Developing white consciousness through a transformative learning process. - Carole Barlas (Adult Education Research Conference, 1997)
This qualitative case study sought to examine a process of group learning in which individuals and group experienced a transformative change in consciousness about white privilege. This study resulted in understanding one process for expanding capacities for continued transformational learning.